ASPECTS REGARDING INFLUENCE OF IPR AND OPR CURVES ON GAS LIFT PERFORMANCE - Mariea Marcu (Romanian Journal of Petroleum & Gas Technology, 2020)
Gas lift performance curve describes the relationship between the gas injection rates and liquid rates produced by a gas lift well and represents the input of the gas lift optimization process. This curve can be obtained by simulation, based on nodal analysis or can be built on the basis of gas injection rates and liquid rates measured in field. To perform nodal analysis, when the nodal point is chosen at the middle of perforations it is necessary to build the IPR (Inflow Performance Relationships) curves which characterize the flow performances of fluid from reservoir into borehole and the OPR (Outflow Performance Relationships) curves, which characterize the upward two-phase flow through tubing. From nodal analysis result the coordinates of the operating points (flowing pressure, liquid rate) for each considered value of gas injection rate. Therefore, we can build the gas lift performance curve by simply plotting the liquid rates as a function of the gas injection rates; these being obtained from nodal analysis. If we study all the steps in the building process of gas lift performance curve, starting with the IPR curves, several errors generated by the bad calibrations may occur and lead to inaccurate results. In our paper we study some methods to build the IPR curves and also we investigate how much these curves influence the gas lift performance curve. From our sensitivity study it resulted that the gas lift performance curve is influenced by the methods used to build the IPR and OPR curves. It is also important to have a good calibration of IPR curves based on more than one test data and of OPR curves based on measured pressures data.